Depositional Controls on Detrital Zircon Provenance: An Example From Upper Cretaceous Strata, Southern Patagonia - Dobbs, Stephen C.; Malkowski, Matthew A.; Schwartz, Theresa M.; Sickmann, Zachary T.; Graham, Stephan A. (Frontiers in Earth Science, 2022)
Understanding how depositional environments within a sedimentary system redistribute and sequester sediment is critical for interpreting basin-scale provenance trends. However, sedimentary source-to-sink models commonly examine temporal changes and do not consider how variation in sedimentation processes across a dispersal pathway may result in contrasting provenance signatures. In this paper, we demonstrate a down-paleoslope shift in detrital zircon provenance signatures correlated with shallow-marine lithofacies patterns from the Upper Cretaceous La Anita Formation and underlying continental slope lithofacies of the Alta Vista Formation (Magallanes-Austral Basin, southern Patagonia). New stratigraphic, sedimentologic, and lithofacies analysis results from the La Anita Formation suggest an upward shoaling succession, from a (i) storm-influenced shoreface, (ii) fluvially-dominated, wave-influenced delta, and a (iii) high-energy, gravelly foreshore. Stratigraphic sections are paired with U-Pb detrital zircon sandstone samples (N = 20; n = 5219), which provide both maximum depositional ages and provenance characteristics. While all samples contain abundant zircon derived from the Andean volcanic arc (ca. 145–75 Ma), the amount from both Jurassic distal volcanic massifs (ca. 188–162 Ma) and recycled orogenic sources exhumed during the advance of the Cretaceous fold-and-thrust belt (>200 Ma; 157–142 Ma) vary with changes in depositional environment. We argue that down-paleoslope, systematic enriching of local fold-and-thrust belt material within the La Anita Formation is reflective of progressive mixing of grains transported via shallow-marine processes, while distally enriched fluvio-deltaic transported zircons were sourced from large, regional catchments. This suggests that competition between transport processes across a shallow and marginal marine sequence of rocks affects the resulting provenance signatures recorded within a single stratigraphic succession. These data also detail the degree of sediment pathway connectivity between shallow-marine sources and deep-marine sinks. Detrital zircon results from muddy continental slope facies of the Alta Vista Formation are made up entirely locally derived material, while zircon results from deep-water, sand-rich channel facies of the Formation are indistinguishable from coeval fluvio-deltaic zircon signatures. This implies that continental shelf-to-slope connectivity in a sediment dispersal system, via submarine canyons or shelf-edge delta progradation, is necessary for detrital zircon distributions from the shallow-marine realm to propagate into the deeper marine.